Pengaruh Metode Menghafal Terhadap peningkatan Aspek Kognitif Siswa di TK Kemala Bhayangkari 03 Selong - Rohliana (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
Humans are born into the world equipped with motor skills that make it easier for humans to adapt to their environment as the beginning of the learning process to gain knowledge. A suitable method in teaching and learning activities will make it easier for students to adapt to the lessons presented so that they can be understood easily. Ultimately, the learning and educational goals will be achieved. One of the methods used to deliver lessons is the memorization method. This method is believed to be a form of assimilation of the child's brain with its new environment (new lessons or unknown theories). With the memorization method, students are expected to be able to remember new lessons or theories and then process them to the next level in the cognitive aspect. The problems that are the focus of this research are two kinds, first is about whether there is an influence of the memorization method on the improvement of students' cognitive aspects in Kemala Bhayangkari 03 Selong Kindergarten, and the second is the magnitude of the influence of memorization method on the improvement of students' cognitive aspects in Kemala Bhayangkari 03 Selong Kindergarten. The population of this study was 131 students of Kemala Bhayangkari 03 Selong Kindergarten, while the research sample was 50%, namely 66 people. Data collection techniques used are observation, questionnaire, interview and observation. The data analysis technique used is product-moment correlation statistical analysis. The study's results showed an effect of the memorization method on improving the cognitive aspects of students at Kemala Bhayangkari 03 Selong Kindergarten, although with a relatively low interpretation.